A. Riegl’s Theory of Artistic Will - Surgailienė, Laima (Problemos, 1986)
A. Riegl’s conception of the development of visual art is discussed in the article. The links between his theory and the conception of art of the 19th century are analysed. The origins of the central concept, that of artistic will, conditioning the evolution of the forms of art is considered. At the same time the one-sidedness of the positivistic orientation of the theory is criticized.